The State of the Metaverse in Education: A Narrative Review of Trends, Applications, Challenges and the Emerging Role of Family–School Interactions - Mohammadi, Delaram; Ebrahimi, Omid (Journal of Psychological Perspective, 2025)
This study explores the evolving role of the metaverse in education, with a particular focus on emerging trends, pedagogical applications, and the transformative potential of family-school interactions within virtual learning environments. This study examined articles from January 2000 to May 2025 using a narrative review method. The statistical population of the study includes all studies conducted on education in the metaverse, and through content analysis, research trends, patterns, geographical distribution, opportunities, and challenges of education in the metaverse were examined. Through a comprehensive review, we identify three dominant trends: (1) increasing adoption of immersive technologies in STEM and arts education, (2) growing research interest post-pandemic, particularly in North America and East Asia, and (3) the development of multi-layered educational interactions (student-teacher, peer-to-peer, and parent-school). Key applications demonstrate the metaverse's capacity to enable borderless collaboration, personalized learning through AI analytics, and culturally inclusive educational experiences. The analysis reveals significant opportunities for family engagement, including real-time parental participation in learning processes and enhanced safety monitoring features. However, critical challenges emerge, including digital equity gaps (particularly in Middle Eastern and African contexts), privacy concerns, technological addiction risks, and special needs accessibility barriers. The findings suggest that while the metaverse offers innovative pathways for reimagining education, its successful integration requires addressing infrastructural limitations, developing ethical frameworks, and implementing targeted teacher and parent training programs. This review contributes to ongoing discussions about digital transformation in education by highlighting both the disruptive potential and implementation complexities of metaverse technologies in family-school ecosystems.